INTEREST OF VILLAGE COMMUNITY TO BECOME MEMBER OF A COOPERATIES: ROLE OF TRUST AND SERVICE QUALITY - Nyoman Dwika Ayu Amrita; I Made Putra Yasa (Jurnal Sains, Ekonomi, Manajemen, Akuntansi dan Hukum, 2023)
This study aims to determine the influence of trust and service quality on people's interest in becoming a member of a cooperative. This research was conducted at the Mertanadi Farmers’ Cooperative in Pelaga Village, Petang District, Badung Regency. Sample determination was carried out using non-random sampling, and data were collected thorough interviews, questionnaires, observations and documentation. The sample in this study was 55 respondents. The questionnaire was then tabulated and tested for validity and reliability. The classic assumption test is carried out after the data meets the conditions of validity and reliability. Furthermore, the data were analysed using multiple linear regression analysis with the help of SPSS. The results showed that partially trust and service quality had a positive and significant effect on the interest of the community in becoming a cooperative member at the Mertanadi Farmers’ Cooperative in Pelaga Village. The results of the study also showed that simultaneously trust and service quality had a positive and significant effect on the interest of the community in becoming a cooperative member at the Mertanadi Farmers’ Cooperative in Pelaga Village.